Capital Structure and Financial Performance of Micro-Finance Institutions in Kenya - Kwena, Irene Atsiech; Githui, Thomas; Kihara , Allan (International Journal of Finance, 2023)
Purpose: This research was envisioned to assess the influence of the capital structure on ROE of Micro-financial institutions in Kenya. The research was in search for resolving the following problem; is there a connection between the composition of capital (loan, shareholder's equity, retained earnings and deposits) and the viability of MFIs? If the firm size has an influence on ROE? The study was motivated by the following capital structure theories, which are the theory of pecking order, Trade-off theory and the theory of Marketing timing. Methodology: To define the independent variable, the researcher used a correlation research design. The target demographic of the research was all 14 successful microfinance companies as recognized by the Kenya Microfinance Act as of 2020. The research therefore represented a census survey with a period of 5 years (from 2016-2020). The study's research model consisted of the independent variable loans, shareholder's equity, retained earnings and deposits and the size of the firm as a moderating variable, determined by the firm's total asset value, and the following ratios as dependent variables: return on equity. To analyze the results, EViews was used. There was descriptive and inferential statistics execution. Diagnostic results were computed before the data analysis. Findings: The results were presented in the form of tables. The inferential statistics with the moderating variable revealed that loan financing has statistical negligible sway on the financial return of MFIs (p=0.9832>0.05). Shareholders equity financing was found to have a statistically significant influence on financial performance of MFIs (p=0.0047<0.05). Retained earnings financing was found to have a statistically significant influence on financial performance of MFIs (p=0.0016<0.05). Deposit financing was found to have a statistically insignificant influence on financial performance of MFIs (p=0.2168>0.05).in this study. Unique contribution to theory, practice and policy: The study suggested that MFIs should strike a balance benefits and costs of debt arising thereof in line with the Trade-off theory, fast growing MFIs to utilize more retained earnings in capital structure, more profitable businesses use less shareholder's equity in capital structure mix and finally positive correlation on deposits indicating similar correlation is likely to exist with financing capital structure. Thus MFIs may consider reviewing these measures so as to enhance performance to serve the low-income earners better in improving the economy. Further studies can be done based on other performance measures like ROA, EPS,Net Interest Margin. The study used a correlation research design for five-year period from 2016 to 2020. Therefore, this study can be replicated using a different methodology and covering a longer period like ten year.